The importance of the laser pulse-ablator interaction dynamics prior to the ablation plasma phase in inertial confinement fusion studies. (13th November 2020) - Kaselouris, E.; Fitilis, I.; Skoulakis, A.; Orphanos, Y.; Koundourakis, G.; Clark, E. L.; Chatzakis, J.; Bakarezos, Μ.; Papadogiannis, N. A.; Dimitriou, V.; Tatarakis, M.
Abstract : This work presents studies which demonstrate the importance of the very early heating dynamics of the ablator long before the ablation plasma phase begins in laser driven inertial confinement fusion (ICF) studies. For the direct-drive fusion concept using lasers, the development of perturbations during the thermo-elasto-plastic (TEP) and melting phases of the interaction of the laser pulse with the ablator's surface may act as seeding to the subsequent growth of hydro-dynamic instabilities apparent during the acceleration phase of the interaction such as for instance the Rayleigh–Taylor and the Richtmyer–Meshkov, which strongly affect the implosion dynamics of the compression phase. The multiphysics-multiphase finite-element method (FEM) simulation results are experimentally validated by advanced three-dimensional whole-field dynamic imaging of the surface of the ablator allowing for a transverse to the surface spatial resolution of only approximately 1 nm. The study shows that the TEP and melting phases of the interaction are of crucial importance since transverse perturbations of the ablator's surface can reach tens of nanometres in amplitude within the TEP and melting phases. Such perturbations are of Rayleigh type and are transferred from the ablator to the substrate from the very first moments of the interaction. This article is part of a discussion meeting issue 'Prospects for high gain inertial fusion energy (part 1)'.